Odor alters color preference in a foraging jumping spider. (23rd May 2018) - Vickers, Michael E; Taylor, Lisa A
Abstract: In many prey taxa with aposematic coloration, prey defenses also involve signals in other modalities (odors, sounds, etc.), yet the selective forces that have driven multimodality in warning displays are not well understood. One potential hypothesis that has recently received support in the avian literature (but has yet to be examined in invertebrates) is that different signal components may interact synergistically, such that one component of a signal (odor) may trigger a predator's aversion to another component of a signal (color). Here, we gave jumping spiders ( Habronattus trimaculatus ) the choice between red or black prey (artificially colored termites) in either the presence or absence of odor from the chemically defended coreid bug ( Acanthocephala femorata ). When the odor was present, spiders were more likely to avoid the color red compared with when the odor was absent. Interestingly, this pattern only held up when the odor was novel; subsequent exposure to the odor had no effect on color preference. Moreover, this pattern only held for the color red (a color typically used as a warning color and often paired with odor). We replicated this experiment giving spiders the choice between green or black prey, and found that the presence of the odor had no effect on the spiders' responses to the color green. We discuss these findings in the context of predator psychology and the evolution of prey coloration. Abstract : Many animals use both bright colors and noxious odors to keep predators away, yet it is not clear why such combinations of colors and odors are so effective. Here, we show that voracious jumping spiders are more likely to avoid prey of certain colors (specifically, red prey) when an aversive odor is present. This may help explain why certain colors and odors frequently evolve together.